2015
DOI: 10.1148/radiol.15141269
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension: A Nomogram Based on CT Pulmonary Angiographic Data for Prediction in Patients without Pulmonary Embolism

Abstract: Cardiovascular data derived from CT pulmonary angiography are associated with PH, and a nomogram can be created that may facilitate identification of PH after exclusion of acute pulmonary embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…We read with considerable interest the article by Dr Aviram and colleagues in the October 2015 issue of Radiology entitled "Pulmonary Hypertension: A Nomogram Based on CT Pulmonary Angiographic Data for Prediction in Patients without Pulmonary Embolism" (1). They showed that cardiovascular data derived from computed tomographic (CT) pulmonary angiography were associated with pulmonary hypertension (PH), and they created a nomogram based on patient age and CT pulmonary angiographic data that may facilitate identification of PH in patients who do not have acute pulmonary embolism.…”
Section: Editormentioning
confidence: 99%
See 1 more Smart Citation
“…We read with considerable interest the article by Dr Aviram and colleagues in the October 2015 issue of Radiology entitled "Pulmonary Hypertension: A Nomogram Based on CT Pulmonary Angiographic Data for Prediction in Patients without Pulmonary Embolism" (1). They showed that cardiovascular data derived from computed tomographic (CT) pulmonary angiography were associated with pulmonary hypertension (PH), and they created a nomogram based on patient age and CT pulmonary angiographic data that may facilitate identification of PH in patients who do not have acute pulmonary embolism.…”
Section: Editormentioning
confidence: 99%
“…The model is based on the patient's age and four CT-derived measurements (ie, right atrial volume, reflux grade, pulmonary artery diameter, and the ratio between the diameter of the pulmonary artery and the aorta) (1). We built this model on one cohort of patients who underwent CT pulmonary angiography This copy is for personal use only.…”
Section: Disclosures Of Conflicts Ofmentioning
confidence: 99%
“…The differential diagnosis for the etiologies of a small LA, however, is limited and includes acute and chronic pulmonary embolism (PE) [4,5] and chronic obstructive pulmonary disease (COPD) [6]. We have previously adopted a technology of 4-chamber volumetric analysis (4CVA) [7,8] in order to explore the cardiac chambers' size as assessed by computed tomography pulmonary angiography (CTPA) in patients with acute PE. Utilizing this software we found that among patients with acute PE a decreased LA volume was associated with an increased 30-day mortality [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nomograms found many applications in the reporting of binary logistic regression models (for recent examples, see [3,4]). A nomogram can not only improve insights of clinicians into the results of a logistic model, it can also be used to arrive at a predicted probability of outcome(s) of interest that is (are) tailored to the profile of an individual patient in a graphical manner.…”
Section: Introductionmentioning
confidence: 99%